Factores comunes relacionados al desarrollo de la presbicia prematura en pacientes de 38 a 40 años de optical visión ecuatoriana, Cantón La Troncal, Provincia Cañar, mayo – septiembre 2019 - Zambrano Mazzini, Kamila Alejandra (2019)
Introduction: Presbyopia is the refractive state of the eye, or eyestrain, which is due to the reduction of the accommodation power of the eye, which causes a decrease in the ability to focus on nearby objects, usually appears after 40 years. Objective: To determine the common factors related to the development of premature presbyopia in patients aged 38 to 40 years of Ecuadorian Optical Vision, La Troncal canton, Cañar province, May - September 2019. Methodology: For the present study a quantitative methodology is found, through an observational analytical study, it was descriptive, cross-sectional, which determined the number of people presenting premature presbyopia in relation to the study population. Results: Regarding the sociodemographic data of the crossing of age - sex variables, a predominance of the female sex is determined with 54% in women and 46% in men, women in the age of 40 years present a greater symptom of visual fatigue with 21%, the APP is one of the ophthalmological consequences that affect vision, causing near visual acuity. Conclusions: The mayor age range of premature presbyopia in patients attending a consultation in Optical Vision Ecuador was higher in women of 39 years, the predominant refractive state is hyperopia in men of 39 years with 36% followed by myopia in women with 14%, the predominant personal pathological history in women with 23%.